Knowledge-based disk scheduling policy using fuzzy logic - Abu Talip, Mohamad Sofian; Hassan Abdalla Hashim, Aisha; Aburas, Abdurazzag Ali; Alam, A. H. M. Zahirul; Asif, Ahmed (2010)
This paper presents the design of 16-element linear array for smart antenna application. Conventional patch antenna is optimized to operate at 1.85GHz (3G applications) by using CST Microwave Studio parameterization. Accurate inter-element spacing has been designed to remove the mutual coupling which causes shifting of the maximum beam pattern towards undesired locations and shifting of the resonant frequency to higher frequency ranges. Narrow beams are also attainted by implementing the complex weights created by LMS beamforming algorithm.